Contribution to Biodiversity Hotspot: Assessment of Forest Types, Floristic Composition and Economic wealth of Nokrek Biosphere Reserve in Northeast India - Singh, Bikarma; Singh, Bishander; Borthakur, S. K.; Phukan, S. J. (Indian Forester, 2018)
Himalayan ecoterrains are globally known as hub and store house of Asian endemic taxa, and the diversity within ecosystems varies from tropical to alpine meadows. Investigation on assessment of vegetation compositions, forest types and floristic analysis of Nokrek biosphere reserve (NBR) in Northeast India were carried out in eight successive years between 2007 and 2015. Two hundred line transects were laid down randomly of 50m x 10m and in total 1406 species 6 subspecies 8 varieties of957 genera and 155 families identified from NBR. Out of the total species studied, 991 species are dicotyledons, and 294 species are monocotyledons. In addition, 113 species of lycophytes and ferns and 8 species of gymnosperms are also documented. In terms of species diversity, Orchidaceae is the most dominant family represented by 141 species, followed by Poaceae (91 spp.), Euphorbiaceae (56 spp.) and Rubiaceae (54 spp.). The present communication deals with information on forest types, floristic compositions and economic valued plants of NBR. Jhum cultivation, coal mining and lime stone extraction are the main human activities exploiting the natural ecosystem of this biosphere reserve. This research will be helpful in formulating future conservation strategies for endangered taxa of Nokrek and adjoining areas.